PENGARUH ANGGARAN PENDIDIKAN TERHADAP PEMBANGUNAN PENDIDIKAN INDONESIA - Ratna Christianingrum (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2018)
An evaluation was needed to see if there were significant changes to national development, after the implementation of article 31 of UUD 1945. This budget allocation is able to influence the education development in Indonesia, especially provision and equity of access to quality education. But the physical development carried out has not been followed by an increase in quality education services. A large education budget allocation is also not followed by an improvement in the quality of education.